Green synthesis, characterization and catalytic activity of natural bentonite-supported copper nanoparticles for the solvent-free synthesis of 1-substituted 1H-1,2,3,4-tetrazoles and reduction of 4-nitrophenol - Rostami-Vartooni, Akbar; Alizadeh, Mohammad; Bagherzadeh, Mojtaba (Beilstein Journal of Nanotechnology, 2015)
In this study, Cu nanoparticles were immobilized on the surface of natural bentonite using Thymus vulgaris extract as a reducing and stabilizing agent. The natural bentonite-supported copper nanoparticles (Cu NPs/bentonite) were characterized by FTIR spectroscopy, X-ray diffraction (XRD), X-ray fluorescence (XRF), field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and Brunauer–Emmett–Teller (BET) analysis. Afterward, the catalytic performance of the prepared catalyst was investigated for the solvent-free synthesis of 1-substituted 1H-1,2,3,4-tetrazoles and reduction of 4-nitrophenol (4-NP) in water. It was found that the Cu NPs/bentonite is a highly active and recyclable catalyst for related reactions.
Keywords: heterogeneous catalyst; modified bentonite; nanocomposite; 1-substituted 1H-1,2,3,4-tetrazoles